SISTEM PENGENDALIAN INTERN TERHADAP DANA RESES PADA KANTOR SEKRETARIAT DPRD BANYUMAS - Lufiana Sanjaya; Iwan Fakhruddin; Novi Dirgantari (Review of Applied Accounting Research (RAAR), 2021)
The Recess Fund Internal Control System starts from the stipulation of the banmus decision letter,board members deposit the number of constituents and the number of places for calculating theamount of funds that will be used by each board member, transfers are made directly from thefinance department to partners, after the recess the board members collect the files accountability,then accounted for at the plenary meeting and later examined by the auditors of the BanyumasGovernment. Internal control of recess funds at the Banyumas DPRD Secretariat has been carriedout in accordance with the provisions in the Banmus decision letter and is also in accordance withthe order in force at the Banyumas DPRD Secretariat. However, in reality, there are still someobstacles, this results in the disbursement of funds taking longer or making work twice. In addition,there are some delays in collecting accountability documents. The flow chart or process diagramrelated to the recess already exists, it's just that it's still unclear and still raises some questions.For this reason, it is better to stipulate the provisions related to recess, so that the process andimplementation is more regular.